(untitled) (Journal of Innovative Solutions for Eco-Environmental Sustainability, 2025)
Glycoglycerolipids are amphiphilic compounds found in cyanobacteria, algae, and plants that have attracted significant attention for their therapeutic potential, particularly as anticancer agents. These lipids, primarily located in the thylakoid membranes of chloroplasts, selectively interact with biological molecules, exhibiting anticancer, antiviral, and anti-inflammatory properties. Among them, monogalactosyldiacylglycerol (MGDG) is notable for its ability to inhibit cancer cell proliferation through mechanisms such as DNA-polymerase inhibition, mitotic centromere-associated kinesin suppression, and killer T-cell activation. While plant-derived MGDGs have been well-studied, their counterparts from microalgae remain underexplored. This study aimed to isolate MGDGs from the green unicellular microalgae Chlorella vulgaris and Neochloris oleoabundans and evaluate their anticancer potential. Microalgae were cultivated in a 3L photobioreactor under blue-red light illumination for 14 days. Total lipids were extracted using the Bligh and Dyer method, and MGDGs were purified through column chromatography with the gradient elution method. HPLC was employed to identify and quantify MGDGs in lipid fractions. NMR spectroscopy revealed unique structural features of C. vulgaris-derived MGDG, which may explain its bioactivity. In vitro MTT assays showed that MGDGs (dissolved in dimethyl sulfoxide (DMSO)) derived from C. vulgaris and N. oleoabundans significantly reduced the viability of MCF-7 breast cancer cells to 4.2% and 7.3%, respectively, at a concentration of 10,000 ng/ml. Combining MGDGs with 5-aminolevulinic acid reduced cell viability, with viability dropping to as low as 0.4% and 0.6%. Plant-derived MGDG (parsley) served as a standard, resulting in 16% cell viability. Notably, DMSO alone reduced cancer cell viability to approximately 70%. These results highlight the promising anticancer potential of MGDGs from microalgae and emphasize the need for further investigation into their therapeutic applications.